Di kita ma-reach ([s.l.] Ecorp Films, 2002)
Xinia, the only child of Fiscal Palma, is a graduating coed completing her thesis in psychology. While conducting her study, she meets Ben, an expert billiard player who lives in the slums. As the two spend more time together, they could not help but feel attracted to each other. When Fiscal Palma learns of this, she immediately orders her daughter to stay away from Ben. Soon Fiscal Palma gets a case involving influential syndicates. In their desperation, the syndicate kidnaps Xinia to make sure that they get a favorable decision. Upon hearing this, Ben immediately sets out rescue Xinia.
VCD
LJ Moreno, Mikey Macapagal Arroyo
Keywords: Feature films